A blue-light-activated GTP-binding protein in the plasma membranes of etiolated peas. - Warpeha, K M (1991)
Heterotrimeric GTP-binding regulatory proteins (G proteins) have been identified as part of signal transduction systems in a wide variety of organisms. In this paper, we establish the presence of a G protein associated with the plasma membranes of the apical bud of etiolated peas. The GTPase activity is induced by low fluences of blue light administered to plasma membrane-enriched fractions. The activity is not responsive to red-light irradiation and is specific for GTP. The threshold for the excitation of the GTPase activity in vitro is less than 10(-1) mumol.m-2 of blue light, consistent with participation in the blue low-fluence system identified in the same tissue. A 40-kDa polypeptide is recognized by polyclonal antisera directed against the alpha subunit of the G protein transducin. The polypeptide also serves as a substrate for ADP-ribosylation by cholera and pertussis toxins. The ability of the 40-kDa polypeptide to serve as substrate for the toxin-mediated ribosylation is mediated by blue-light irradiation, implying that the 40-kDa polypeptide is the alpha subunit of a blue-light-stimulated G protein. The 40-kDa polypeptide binds a nonhydrolyzable photoaffinity-labeling analog of GTP only after irradiation with blue light. The protein we have described may function as an alpha subunit of a G protein active in the process of light-mediated development in higher plants.